Interstage mortality after the Norwood procedure: Results of the multicenter Single Ventricle Reconstruction trial - Ghanayem, Nancy S; Allen, Kerstin R; Tabbutt, Sarah; Atz, Andrew M; Clabby, Martha L; Cooper, David S; Eghtesady, Pirooz; Frommelt, Peter C; Gruber, Peter J; Hill, Kevin D; Kaltman, Jonathan R; Laussen, Peter C; et al. (The Journal of thoracic and cardiovascular surgery, 2012)
For infants with single ventricle malformations undergoing staged repair, interstage mortality is reported at 2% to 20%. The Single Ventricle Reconstruction trial randomized subjects with a single morphologic right ventricle undergoing a Norwood procedure to a modified Blalock-Taussig shunt (MBTS) or a right ventricle-to-pulmonary artery shunt (RVPAS). The aim of this analysis was to explore the associations of interstage mortality and shunt type, and demographic, anatomic, and perioperative factors. Participants in the Single Ventricle Reconstruction trial who survived to discharge after the Norwood procedure were included (n = 426). Interstage mortality was defined as death postdischarge after the Norwood procedure and before the stage II procedure. Univariate analysis and multivariable logistic regression were performed adjusting for site. Overall interstage mortality was 50 of 426 (12%)-13 of 225 (6%) for RVPAS and 37 of 201 (18%) for MBTS (odds ratio [OR] for MBTS, 3.4; P < .001). When moderate to severe postoperative atrioventricular valve regurgitation (AVVR) was present, interstage mortality was similar between shunt types. Interstage mortality was independently associated with gestational age less than 37 weeks (OR, 3.9; P = .008), Hispanic ethnicity (OR, 2.6; P = .04), aortic atresia/mitral atresia (OR, 2.3; P = .03), greater number of post-Norwood complications (OR, 1.2; P = .006), census block poverty level (P = .003), and MBTS in subjects with no or mild postoperative AVVR (OR, 9.7; P < .001). Interstage mortality remains high at 12% and is increased with the MBTS compared with the RVPAS if postoperative AVVR is absent or mild. Preterm delivery, anatomic, and socioeconomic factors are also important. Avoiding preterm delivery when possible and close surveillance after Norwood hospitalization for infants with identified risk factors may reduce interstage mortality.